Diversidade cultural: as práticas pedagógicas de professoras da educação infantil do povo Pitaguary - Lima, Fabiana Mendonça (2019)
This research addresses the cultural diversity in Early Childhood Education, having as its central theme the Indigenous Early Childhood Education and the pedagogical practices of its teachers. We investigate the way teachers' pedagogical practices Kindergarten (2 years) and Children's V (5 years), of Curumim Indigenous Municipal School are related to the expressions of culture from the knowledge, beliefs, values, worldviews and memories of the Pitaguary people. We carried out research activities with two preschool teachers mentioned classes, from the Municipality of Maracanaú-CE. The approach is qualitative, with an ethnographic case study. We used as research instruments the observation, questionnaire and semi-structured interview with the teachers, research subjects. The theoretical framework consisted of the writings of Zabalza (1998) Abramowicz (2013), Franco (2015), Freire (1996, (2011), Oliveira-Formosinho (2007), Laraia (1986), Brougère (2010), Moreira and Tadeu (2013), among others. The field research consisted in the accomplishment of a questionnaire, with the objective of tracing the subjects profile; observations of teachers' pedagogical practices, as well as the general dynamics of the school and community festivities; and in the application of interviews with the teachers. The data collected from the field diary, questionnaires and interviews were analyzed from a critical and reflective view of education (SARMENTO, 2011, FARIAS, 2010). Finally, the results point to some elements: the need for reflection on indigenous issues, from a contextualized look; the perception of a culture that changes but does not forget its roots; a school that reflects pedagogical practices in early childhood education that reinvent themselves daily, presenting limits and possibilities in the relationship of culture with these practices; and also the recognition of a culture that has much to contribute to those who study and live with children in the context of early childhood education